2021
DOI: 10.3390/ijms221910260
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors, PI3K/AKT/mTOR and MAPK Signaling Pathways in Colorectal Cancer Pathogenesis: Where Are We Now?

Abstract: Colorectal cancer (CRC) is a predominant malignancy worldwide, being the fourth most common cause of mortality and morbidity. The CRC incidence in adolescents, young adults, and adult populations is increasing every year. In the pathogenesis of CRC, various factors are involved including diet, sedentary life, smoking, excessive alcohol consumption, obesity, gut microbiota, diabetes, and genetic mutations. The CRC tumor microenvironment (TME) involves the complex cooperation between tumoral cells with stroma, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 183 publications
(256 reference statements)
3
96
0
Order By: Relevance
“…Many growth factors and their receptors have been extensively studied for both their role in HNC pathophysiology and possible target therapy development. One of the most studied is the epidermal growth factor receptor (EGFR) [ 116 , 117 , 118 , 119 , 120 ], a transmembrane tyrosine kinase receptor of the ErbB family that promotes multiple signaling pathways involved in tumor cell growth, evasion, angiogenesis, and invasion [ 121 ]. The EGFR activation in HNC is mainly driven by the high expression of its soluble ligands (EGF and transforming growth factor-alpha (TGF-α)), resulting in the dimerization of EGFR, the autophosphorylation of its intracellular kinase domain, and the stimulation of a proliferative and pro-survival intracellular signaling through the mitogen-activated protein kinase (MAPKs) cascade (as well as the PI3K-AKT-mTOR and JAK-STAT pathways) [ 122 ].…”
Section: Head and Neck Cancer Etiopathogenesismentioning
confidence: 99%
“…Many growth factors and their receptors have been extensively studied for both their role in HNC pathophysiology and possible target therapy development. One of the most studied is the epidermal growth factor receptor (EGFR) [ 116 , 117 , 118 , 119 , 120 ], a transmembrane tyrosine kinase receptor of the ErbB family that promotes multiple signaling pathways involved in tumor cell growth, evasion, angiogenesis, and invasion [ 121 ]. The EGFR activation in HNC is mainly driven by the high expression of its soluble ligands (EGF and transforming growth factor-alpha (TGF-α)), resulting in the dimerization of EGFR, the autophosphorylation of its intracellular kinase domain, and the stimulation of a proliferative and pro-survival intracellular signaling through the mitogen-activated protein kinase (MAPKs) cascade (as well as the PI3K-AKT-mTOR and JAK-STAT pathways) [ 122 ].…”
Section: Head and Neck Cancer Etiopathogenesismentioning
confidence: 99%
“…Of note, we revealed that the inflammatory cytokines were able to activate macrophages that, in turn, could amplify inflammation, resulting in a tumor-promoting microenvironment that could exacerbate the risk of cancer development [ 9 , 49 ]. Among pro-inflammatory pathways, we investigated ERK1/2 and mTOR, as the first one has been demonstrated to be involved in several inflammatory disorders, such as psoriatic arthritis (PsA) or rheumatoid arthritis (RA) and IBD [ 15 , 50 , 51 ], while mTOR was reported to be constitutively activated in active celiac disease (ACD) as well as IBD [ 13 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed whether the release of cytokines or chemokines correlated with the activation of pro-inflammatory pathways such as extracellular signal-regulated protein kinase 1/2 (ERK1/2) and mammalian target of rapamycin (mTOR). Indeed, both have been shown to play an important role in IBD [ 13 , 14 , 15 ], which, as previously mentioned, strongly increases colon cancer risk [ 16 ]. Besides, we wondered if Hydroxytyrosol could counteract all the observed B[a]P-mediated effects.…”
Section: Introductionmentioning
confidence: 99%
“…Receptor tyrosine kinases (RTKs) play an important role in several cellular processes in tumors including growth, migration, invasion, and the response to therapies [ 5 ]. For instance, the mitogen-activated protein kinase (MAPK) pathway and the phosphoinositide-3-kinase–protein kinase B/Akt (PI3K-PKB/Akt) pathway, two main intracellular pathways activated by the epidermal growth factor receptor (EGFR), were the most used therapeutic targets in metastatic colon cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%